Islamic Finance and Charity in The Muslim World. The Role of The Islamic Development Bank in Financing Aid - Altea Pericoli (Journal of Economics and Business Aseanomics (JEBA), 2020)
The purpose of this paper is to describe the role of Islamic finance in the charitable sector by analysing how Islamic banks and States manage funds for humanitarian and development aid. The Islamic Development Bank (IsDB) represents one of the main Islamic actors involved in the development cooperation and humanitarian relief and, in partnership with other donors, it  implements programs in its member countries. This research examines the existing literature and data regarding projects financed by the IsDB with the aim to understand the impact of Islamic financial tools on aid. The Lives and Livelihoods Fund (LLF) is an example of a program for poverty alleviation but also a mechanism of blended finance for supporting health, agriculture, and infrastructure projects. Financed by the IsDB, bilateral institutions, and foundations,it uses an innovative financing model aiming to produce sustainable growth in the most vulnerable member countries. It could represent a positive model for financing and implementing aid in a joint effort of Muslim and non-Muslim donors.